PERSEPEKTIF OLAHRAGA TINJU DALAM MENDUKUNG PRESTASI OLAHRAGA KABUPATEN ROKAN HULU - Ridwan Sinurat; Muarif Arhas Putra (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2020)
Boxing is a sport and a martial art that features two participants of similar weight competing with each other by using their fists in a series of one or three minute intervals called rounds. The purpose of this study was to determine the perspective of boxing in supporting sports achievements in Rokan Hulu Regency in terms of aspects of organization and management, funding, government support, human resources, infrastructure, fostering and the application of science and technology. Sources of data came from the Boxing Sport Management Board, KONI Management Board, Rokan Hulu Boxing Athletes and Rokan Hulu Boxing Trainer. Data is analyzed by collecting data, reducing data, conveying data and drawing conclusions. The results of the study 1) already have an organizational legality with proof of decree Number 05 / SK / PERTINA RIAU / V / 2018. 2) the source of funds remains from KONI Rokan Hulu Regency but the assistance is not sufficient, 3) support from the government has not been maximized, 4) human resources are very low only has 1 referee and 1 trainer in the entire Rokan Hulu Regency, 5) infrastructure facilities are very very low far from the standard word, only has 2 pairs of boxing gloves and 1 sansack, 6) only 1 boxing club in Tambusai, 7) Application of Science and technology has never been done, even though Rokan Hulu district has 2 sports campuses namely Pasir Pengaraian University and STKIP Rokania. Suggestions for all lines of community from village, sub-district and district governments to support the existence of boxing in the Rokan Hulu Regency, PERTINA should immediately conduct socialization about boxing in schools in Rokan Hulu and PERTINA also increase the quantity of sports human resources such as participating in sports referee training, licensed trainer. Abstrak Tinju adalah olahraga dan seni bela diri yang menampilkan dua orang partisipan dengan berat yang serupa bertanding satu sama lain dengan menggunakan tinju mereka dalam rangkaian pertandingan berinterval satu atau tiga menit yang disebut ronde. Tujuan penelitian ini adalah untuk mengetahui perspektif olahraga tinju dalam mendukung prestasi olahraga di Kabupaten Rokan Hulu ditinjau dari aspek Organisasi dan manajemen, pendanaan, dukungan pemerintah, sumber daya manusia, sarana prasarana, pembinaan dan Penerapan IPTEK. Sumber data berasal dari Pengurus Cabang Olahraga Tinju, Pengurus KONI, Atlet Tinju Rokan Hulu dan Pelatih Tinju Rokan Hulu. Data dianalisis dengan mengumpulkan data, mereduksi data, menyampaikan data dan menarik kesimpulan. Hasil penelitian 1) sudah memiliki legalitas organisasi dengan bukti surat keputusan Nomor 05/SK/PERTINA RIAU/V/2018. 2) sumber dana tetap dari KONI Kabupaten Rokan Hulu akan tetapi bantuannya tidak mencukupi kebutuhan, 3) dukungan dari pemerintah belum maksimal, 4) sumber daya manusia sangat rendah hanya memiliki 1 wasit dan 1 pelatih Se-Kabupaten Rokan Hulu, 5) sarana prasaran sangat rendah sekali jauh dari kata standart, hanya memiliki sarung tinju 2 pasang dan 1 sansack, 6) hanya 1 klub tinju di tambusai, 7) Penerapan Ilmu Pengetahuan dan teknologi belum pernah dilakukan, padahal kabupaten Rokan Hulu mempunyai 2 kampus olahraga yaitu Universitas Pasir Pengaraian dan STKIP Rokania. Saran kedepanya semua lini masyarakat baik dari pemerintahan desa, kecamatan dan kabupaten untuk mendukung adanya cabang olahraga tinju di Kabupaten Rokan Hulu, PERTINA hendaknya segera melakukan sosialisasi tentang olahraga tinju di sekolah-sekolah sekabupaten Rokan Hulu dan PERTINA juga meningkatkan kuantitas sumber daya manusia keolahragaan seperti mengikuti pelatihan wasit, pelatih yang berlisensi. Kata Kunci: Perspektif dan Tinju